The effect of a magnetic field on the phenolic composition and virus sanitation of raspberry plants - Mikhail Upadyshev; Svetlana Motyleva; Ivan Kulikov; Vladislav Donetskih; Maria Mertvischeva; Klavdia Metlitskaya; Anna Petrova (Horticultural Science, 2021)
A magnetic pulse treatment led to an increase in the Raspberry bushy dwarf Idaeovirus-free microplants' output and their phenolic composition change. The greatest output of the virus-free raspberries microplants (80-82%) was marked after complex treatment with pulsed and rotating magnetic fields with a time-changing frequency from 3.2 to 51 Hz, as well as with a pulsed magnetic field with a frequency from 1 to 10 Hz. The pulsed and rotating magnetic fields' complex effect resulted in the gallic and salicylic acid content increase by 14 % and 71%, respectively, compared to the untreated variant. The chlorogenic, salicylic and gallic acids' active synthesis was observed 72 hours after the magnetic treatment with a frequency from 3.2 to 51 Hz. There was a tendency for the amount of the phenolcarbonic acid to decrease 14 days after the magnetic treatment, except for the variant with the pulsed and rotating field treatment.